Brain network mechanism of acupuncture for chronic spontaneous urticaria: a functional magnetic resonance imaging study protocol - Huang, Xianhao; Xie, Jing; Yang, Yang; Dai, Xuechun; Lu, Lingyun; Li, Ning; Li, Ying; Wang, Song; Zhang, Leixiao (Frontiers in Neurology, 2023)
Introduction: Chronic spontaneous urticaria (CSU) is a common skin condition that can significantly impact patients' quality of life. Although studies have demonstrated the efficacy of acupuncture in treating CSU, the underlying mechanisms remain unclear. Dysfunction within the brain's default mode network (DMN) represents a fundamental characteristic of central pathological changes associated with CSU. Therefore, it is hypothesised that improving brain network dysfunction 2 could serve as a key mechanism through which acupuncture exerts its therapeutic effects. This study aims to provide evidence supporting this hypothesis.This study, a parallel, randomised, sham-controlled functional neuroimaging investigation will be conducted in China. We aim to enrol 50 patients with CSU and 25 healthy controls, distributing them evenly between the acupuncture and sham acupuncture groups in a 1:1 ratio. The total observation period will span six weeks, including two weeks designated for the baseline phase and four weeks allocated for the clinical treatment phase. Prior to treatment, all participants will undergo magnetic resonance scanning, clinical index detection, and microbiota collection. Following treatment, the patients with CSU will be retested for these indicators. Using resting-state functional connectivity (rsFC) analysis, dynamic Functional Connection (dFC) analysis, and brain microstate extraction technology combined with correlation analysis of microbiota and clinical indicators, the regulatory mechanism of acupuncture on the brain network of CSU will be evaluated from multiple dimensions.Ethics and Dissemination: This trial was approved by the Biomedical Ethics Review Committee of the West China Hospital, Sichuan University (No. 2022(No. -1255)). Each participant will provide written informed consent to publish any potentially identifiable images or data.http://www.chictr.org.cn/index.aspx,identifier:ChiCTR2200064563.